Investigating factor to project objectives underachievement in Malaysian landscape architecture project - S.Muthuveeran, Adam Aruldewan; Hassan, Mohd Azren; Yin, Izuandi; Abd Karim, Saipol Bari (Universiti Putra Malaysia, 2023)
Malaysia landscape architecture projects frequently face several difficulties that expose their projects to a high degree of challenges. These challenges will become project issues that eventually affect the achievement of the project objectives. Understanding the factors of project objective underachievement is essential for project practitioners to manage and control their projects in the future. Thus, this study aims to investigate factors to project objectives underachievement in the Malaysian landscape architecture project. Data were gathered through semi-structured interviews with twenty-four landscape architect practitioners from Klang Valley. The interview information was analysed using the content and thematic analysis method. The snowball effect from project challenges to project issues and stakeholders’ factors causes underachievement of the landscape architecture project objective. Managing the project affects the organisation’s operational and cultural objectives directly, whereas the project outcome issues indirectly jeopardise the achievement of the project’s business objectives. The finding will be a lesson learnt for project practitioners to evaluate their current project management practice and recommend issue and stakeholder management applications, enabling the achievement of project objectives.